Pendidikan Negara Dari Marx ke Stalin Studi Pendekakatan Kritis-filosofis dan heuristika - Nabil Nabil (Almarhalah | Jurnal Pendidikan Islam, 2017)
in this century, many people spontaneously label themselves to defend the State because there is an extreme ideology to divide the State in the name of religion, even the events of 1965 returned to the surface as if the State had to apologize for the atrocities and massacres after 1965. Basically, the State was something newly formed from individuals and then groups that have systems, institutions, bureaucracy and usually have sovereignty, both in and out. But in the end it will become absurd when the State is placed above our heads.The state as an independent institution and has political sovereignty, but as an instrument of oppression and administration that can be used for various purposes by the social classes that control its power. Engels saw the instrumentalist view when he saw that State power was always in the hands of a certain social class - the middle class - who used that power in the interests of maintaining economic and political dominance over other social classes.